PENGARUH SISTEM KEPEMIMPINAN, KOMUNIKASI, DAN PENGENDALIAN TERHADAP PERILAKU PELAYANAN DI PUSKESMAS KEDOKANBUNDER KABUPATEN INDRAMAYU - Winda Dwi Yanthi; Rohmatul Fawaiz (PT. Berkah Digital Teknologi, 2025)
Purpose: This study aims to investigate the influence of leadership, communication, and control systems on service behavior at the Kedokanbunder Health Center in Indramayu Regency. Research Methodology: A quantitative approach using questionnaires and interviews. Data was collected from 50 staff members of the Kedokanbunder Health Center. Multiple linear regression analysis was conducted using SPSS software. Results: The results indicate that leadership, communication, and control systems significantly positively influence service behavior at the Kedokanbunder Health Center. The R-squared value of 0.907 shows that 90.7% of the variance in service behavior is explained by the independent variables. Limitations: The study is limited by a sample size of 50 respondents, which may not fully represent the entire population of healthcare workers in the region. Further research with a larger sample size and additional variables is recommended Contribution: This study contributes to the field of healthcare management, particularly in improving service behavior in health centers. The findings provide valuable insights for health administrators and policymakers seeking to enhance service quality through better leadership, communication, and control systems.